The Proliferation and Differentiation of Adult Neural Progenitors with a Novel Biomaterial - Coyle, Matthew J. (Université d'Ottawa / University of Ottawa, 2013)
Endogenous neural progenitor cells (NPCs) have the potential to repair the brain and spinal cord after injury. Using an in vitro neurosphere culture system we evaluated the ability of modifying adult rat spinal cord and subventricular zone progenitor cell differentiation into neurons, oligodendrocytes and astrocytes with retinoic acid, platelet derived growth factor and bone morphogenic protein-4, respectively. NPCs from both regions were exposed to varying concentrations of each factor. We found that SC and SVZ derived cells respond differently to these differentiation factors indicating that the therapeutic controls intended for one region may be different for the other. To assess delivery of potential therapeutic control, we evaluated a poly (lactide-co-glycolide) (PLGA) biomaterial designed to deliver these therapeutic agents to the injured central nervous system. The biocompatibility of PLGA for NPC proliferation, differentiation and survival was assessed using an in vitro neurosphere and differentiation assay. Our assessment of this biomaterial reveals that there were detrimental effects of PLGA degradation at later time points, suggesting, the need to control the degradation rate of this biomaterial, as its by-products -lactic acid and glycolic acid- may hinder the efficacy of delivered therapeutic factors to NPCs following injury.